Comparative dimensions of COVID-19 visual health literacy: social media news imagery in Germany and China - Benjamin Nickl; Kuanyong Qiu; Jordi Vidal-Robert (Humanities & Social Sciences Communications)
Abstract The COVID-19 pandemic prompted governments worldwide to utilise social media news platforms for disseminating critical public health information and safety protocols. Visual aids, including photographs, videos, charts, and infographics, played a key role in conveying health-related messages. However, there are variations in visual communication practices across countries, influenced by local health communication habits and cultural contexts. This study examines these variations in the visual health discourse that emerged in China and Germany during the pandemic, focusing on metaphorical mapping as a central analytical tool. We introduce the concept of “visual dataset fingerprints,” outlining the distinct composition of public health visuals on eight social news media platforms in Germany and China. Our descriptive analysis encompasses over 3700 digital visual media posts related to COVID-19, shared by leading national news media accounts in German, English, and Mandarin on microblogs in 2022. As a preliminary outcome of our study, we observe differences in image use based on the analysis of 1678 media posts by four Chinese outlets and 1329 media posts by four German outlets. These differences may reflect variations in how public opinion, perceptions, and attitudes toward COVID-19 policies are shaped across languages and cultures. Through its comparative visual analysis, our pilot study offers the potential for a new research approach to global healthcare communication in social news media and digital visual cultures.